Supplementation with branched-chained amino acids, glutamine and protein hydrolysates: Rationale for effects on metabolism and performance - Wagenmakers, A. J. M. (1999)
chapter from the online-book "The Role of Protein and Amino Acids in Sustaining and Enhancing Performance"